Textual and Contextual Studies on Education in Surah Al-Fatihah As the Axis of Life - Nur Hadi; Ali Mahfuz Munawar (Presscience, 2023)
The text is an expression of words that are genuinely unchangeable in their alternative meaning. Additionally, the term